INTERDISCIPLINARY LINKS IN GEOGRAPHIC EDUCATION: A SYSTEMATIC REVIEW OF FIELDS OF SCIENCE - Sarsebaeva, Aigul; ABDIMANAPOV, B.; USSENOV, N.; GAISIN, I.; ISSAKOV, Y. (Pedagogy and Psychology, 2024)
In geographical education, interdisciplinary links allow to identify the main elements of educational content, to develop system-forming ideas, concepts, general scientific methods of learning activities, opportunities for students to comprehensively assimilate knowledge from different scientific disciplines. Interdisciplinary links influence the composition and structure of each academic discipline. Therefore, it is very important to highlight the interdisciplinary links that are taken into account in the content of geography and, on the contrary, take place in other scientific disciplines besides geography. The aim of this study was to conduct a systematic review of interdisciplinary related science fields that integrate geographic educational technologies. The study used methods of analysis, differentiation, systematisation to identify the interdisciplinary links between geography and sciences such as history; biology; ecology; mathematics; cartography; physics and chemistry. As a result of the study, it turned out that these branches of science - form a holistic scientific worldview in the student, strengthen interdisciplinary links and enhance cognitive development, abstract thinking, creativity within the integration of different disciplines. Thus, interdisciplinary links in geographical education is a modern teaching principle that influences the selection and structure of teaching material of a number of disciplines, increases the systematicity of students’ knowledge, activates teaching methods and is aimed at the use of integrated forms of learning organisation that ensure the unity of the learning process.